High-efficiency solar oven for tropical countries - Jebaraj, S. (Asian Research Publishing Network, 2015)
In today's society, pollution is becoming an increasing problem. Since the solar energy is a limitless clean free energy that can be harnessed, suggestions have arisen such that solar energy can be incorporated in our daily lives to produce energy to conserve other non-renewable energy. Solar oven refers to a type of oven which uses the sun's energy to cook food inside of it. It has been planned to design a high efficiency solar oven which is convenient and comfortable for all kind cooking, baking and heating with high efficiency without spoiling the foods nutrients. This solar oven is capable of making a temperature change up to 150 Â°C in 60 minutes. Once the prototype was completed, several experiments were conducted to determine the efficiency between two designs which are; without the parabolic dish and with the parabolic dish. With the presence of parabolic dish on top of the box proves that the efficiency increases when compared without using it. It is estimated that the efficiency attained by the solar oven with parabolic collector at 150 minutes is 53.62 whereas, for the same time duration, the solar oven efficiency without parabolic collector is estimated to be 35.86. This solar oven would be very useful to conserve the electricity and healthy food cooking. Â© 2006-2015 Asian Research Publishing Network (ARPN).